Alkyl chain length-dependent surface reaction of dodecahydro-N-alkylcarbazoles on Pt model catalysts - Gleichweit, Christoph; Amende, Maximilian; Bauer, Udo; Schernich, Stefan; Höfert, Oliver; Lorenz, Michael Peter Andreas; Zhao, Wei; Müller, Michael; Koch, Marcus; Bachmann, Philipp; Wasserscheid, Peter; Libuda, Jörg; et al. (Journal of Chemical Physics, 2014)
The concept of liquid organic hydrogen carriers (LOHC) holds the potential for large scale chemical storage of hydrogen at ambient conditions. Herein, we compare the dehydrogenation and decomposition of three alkylated carbazole-based LOHCs, dodecahydro-N-ethylcarbazole (H-NEC), dodecahydro-N- propylcarbazole (H-NPC), and dodecahydro-N-butylcarbazole (H -NBC), on Pt(111) and on AlO-supported Pt nanoparticles. We follow the thermal evolution of these systems quantitatively by in situ high-resolution X-ray photoelectron spectroscopy. We show that on Pt(111) the relevant reaction steps are not affected by the different alkyl substituents: for all LOHCs, stepwise dehydrogenation to NEC, NPC, and NBC is followed by cleavage of the C-N bond of the alkyl chain starting at 380-390 K. On Pt/AlO, we discern dealkylation on defect sites already at 350 K, and on ordered, (111)-like facets at 390 K. The dealkylation process at the defects is most pronounced for NEC and least pronounced for NBC. © 2014 AIP Publishing LLC.

Dicyclohexylmethane as a Liquid Organic Hydrogen Carrier: A Model Study on the Dehydrogenation Mechanism over Pd(111) - Amende, Maximilian; Gleichweit, Christoph; Xu, Tao; Höfert, Oliver; Koch, Marcus; Wasserscheid, Peter; Steinrück, Hans-Peter; Papp, Christian; Libuda, Jörg (Catalysis Letters, 2016)
Abstract: We have studied the dehydrogenation of the liquid organic hydrogen carrier (LOHC) dicyclohexylmethane (DCHM) to diphenylmethane (DPM) and its side reactions on a Pd(111) single crystal surface. The adsorption and thermal evolution of both DPM and DCHM was measured in situ in ultrahigh vacuum (UHV) using synchrotron radiation-based high-resolution X-ray photoelectron spectroscopy (HR-XPS). We found that after deposition at 170 K, the hydrogen-lean DPM undergoes C-H bond scission at the methylene bridge at 200 K and, starting at 360 K, complete dehydrogenation of the phenyl rings occurs. Above 600 K, atomic carbon incorporates into the Pd bulk. For the hydrogen-rich DCHM, the first stable dehydrogenation intermediate, a double π-allylic species, forms already at 190 K. Until 340 K, further dehydrogenation of the phenyl rings and of the methylene bridge occurs, yielding the same intermediate that is formed upon heating of DPM to this temperature, that is, DPM dehydrogenated at the methylene bridge. The onset for the complete dehydrogenation of this intermediate occurs at a much higher temperature than after adsorption of DPM. This behavior is mainly attributed to coadsorbed hydrogen from DCHM dehydrogenation. The results are discussed in comparison to our previous study of DPM and DCHM on Pt(111) revealing strong material dependencies. Graphical Abstract: [Figure not available: see fulltext.]
Keywords: Liquid organic hydrogen carrier; Model catalysis; X-ray photoelectron spectroscopy

Measurement of Hydrogen Solubility in Potential Liquid Organic Hydrogen Carriers - Aslam, Rabya; Müller, Karsten; Müller, Michael; Koch, Marcus; Wasserscheid, Peter; Arlt, Wolfgang (Journal of Chemical and Engineering Data, 2016)
Liquid organic hydrogen carriers (LOHC) are potential compounds that can facilitate chemical energy storage and hydrogen logistics using reversible hydrogenation. For the process development, the physical solubility of hydrogen in potential LOHCs is required. In this work, solubility of hydrogen in the potential LOHC systems toluene/methylcyclohexane, N-ethylcarbazole/perhydro-N-ethylcarbazole, and dibenzyltoluene/perhydrodibenzyltoluene was measured using the static isochoric saturation method. The data were measured at low pressures up to 10 bar within the temperature range of (293 to 373) K. Hydrogen solubility in hydrogenated forms of the LOHCs was found to be higher compared to the dehydrogenated forms. Solubility in all substances increased with increasing temperature within the whole temperature range under consideration. The temperature dependency of the Henry coefficient of hydrogen in the solvents was correlated using the Benson and Krause correlation.

Model catalytic studies of liquid organic hydrogen carriers: Dehydrogenation and decomposition mechanisms of dodecahydro-n-ethylcarbazole on pt(111) - Amende, Maximilian; Gleichweit, Christoph; Werner, Kristin; Schernich, Stefan; Zhao, Wei; Lorenz, Michael Peter Andreas; Höfert, Oliver; Papp, Christian; Koch, Marcus; Wasserscheid, Peter; Laurin, Mathias; Steinrück, Hans-Peter; et al. (ACS Catalysis, 2014)
Liquid organic hydrogen carriers (LOHC) are compounds that enable chemical energy storage through reversible hydrogenation. They are considered a promising technology to decouple energy production and consumption by combining high-energy densities with easy handling. A prominent LOHC is N-ethylcarbazole (NEC), which is reversibly hydrogenated to dodecahydro-N-ethylcarbazole (H -NEC). We studied the reaction of H-NEC on Pt(111) under ultrahigh vacuum (UHV) conditions by applying infrared reflection-absorption spectroscopy, synchrotron radiation-based high resolution X-ray photoelectron spectroscopy, and temperature-programmed molecular beam methods. We show that molecular adsorption of H-NEC on Pt(111) occurs at temperatures between 173 and 223 K, followed by initial C-H bond activation in direct proximity to the N atom. As the first stable dehydrogenation product, we identify octahydro-N-ethylcarbazole (H -NEC). Dehydrogenation to H-NEC occurs slowly between 223 and 273 K and much faster above 273 K. Stepwise dehydrogenation to NEC proceeds while heating to 380 K. An undesired side reaction, C-N bond scission, was observed above 390 K. H-NEC and H-carbazole are the dominant products desorbing from the surface. Desorption occurs at higher temperatures than H-NEC formation. We show that desorption and dehydrogenation activity are directly linked to the number of adsorption sites being blocked by reaction intermediates. © 2014 American Chemical Society.

Regeneration of LOHC dehydrogenation catalysts: In-situ IR spectroscopy on single crystals, model catalysts, and real catalysts from UHV to near ambient pressure - Amende, Maximilian; Kaftan, Andre; Bachmann, Philipp; Brehmer, Richard; Preuster, Patrick; Koch, Marcus; Wasserscheid, Peter; Libuda, Jörg (Applied Surface Science, 2016)
The Liquid Organic Hydrogen Carrier (LOHC) concept offers an efficient route to store hydrogen using organic compounds that are reversibly hydrogenated and dehydrogenated. One important challenge towards application of the LOHC technology at a larger scale is to minimize degradation of Pt-based dehydrogenation catalysts during long-term operation. Herein, we investigate the regeneration of Pt/alumina catalysts poisoned by LOHC degradation. We combine ultrahigh vacuum (UHV) studies on Pt(111), investigations on well-defined Pt/AlO model catalysts, and near-ambient pressure (NAP) measurements on real core-shell Pt/AlO catalyst pellets. The catalysts were purposely poisoned by reaction with the LOHC perhydro-dibenzyltoluene (H18-MSH) and with dicyclohexylmethane (DCHM) as a simpler model compound. We focus on oxidative regeneration under conditions that may be applied in real dehydrogenation reactors. The degree of poisoning and regeneration under oxidative reaction conditions was quantified using CO as a probe molecule and measured by infrared reflection-absorption spectroscopy (IRAS) and diffuse reflectance Fourier transform IR spectroscopy (DRIFTS) for planar model systems and real catalysts, respectively. We find that regeneration strongly depends on the composition of the catalyst surface. While the clean surface of a poisoned Pt(111) single crystal is fully restored upon thermal treatment in oxygen up to 700 K, contaminated Pt/AlO model catalyst and core-shell pellet were only partially restored under the applied reaction conditions. Whereas partial regeneration on facet-like sites on supported catalysts is more facile than on Pt(111), carbonaceous deposits adsorbed at low-coordinated defect sites impede full regeneration of the Pt/AlO catalysts.
Keywords: Infrared spectroscopy; Liquid Organic Hydrogen Carrier; Materials gap; Model catalysis; Pressure gap; Real catalysis

Size and structure effects controlling the stability of the liquid organic hydrogen carrier dodecahydro- N -ethylcarbazole during dehydrogenation over pt model catalysts - Amende, Maximilian; Gleichweit, Christoph; Schernich, Stefan; Höfert, Oliver; Lorenz, Michael Peter Andreas; Zhao, Wei; Koch, Marcus; Obesser, Katharina; Papp, Christian; Wasserscheid, Peter; Steinrück, Hans-Peter; Libuda, Jörg (Journal of Physical Chemistry Letters, 2014)
Hydrogen can be stored conveniently using so-called liquid organic hydrogen carriers (LOHCs), for example, N-ethylcarbazole (NEC), which can be reversibly hydrogenated to dodecahydro-N-ethylcarbazole (H-NEC). In this study, we focus on the dealkylation of H-NEC, an undesired side reaction, which competes with dehydrogenation. The structural sensivity of dealkylation was studied by high-resolution X-ray photoelectron spectroscopy (HR-XPS) on AlO-supported Pt model catalysts and Pt(111) single crystals. We show that the morphology of the Pt deposit strongly influences LOHC degradation via C-N bond breakage. On smaller, defect-rich Pt particles, the onset of dealkylation is shifted by 90 K to lower temperatures as compared to large, well-shaped particles and well-ordered Pt(111). We attribute these effects to a reduced activation barrier for C-N bond breakage at low-coordinated Pt sites, which are abundant on small Pt aggregates but are rare on large particles and single crystal surfaces. © 2014 American Chemical Society.